Planar Edged UWB Antenna for Water Quality Measurement - Joseph Charles Vinoth, Joseph Charles Vinoth; Subramaniam Ramesh, Subramaniam Ramesh; Z. Abidin, Zuhairiah; Suhail A. Qureshi, Suhail A. Qureshi; Sivathanu Chitra, Sivathanu Chitra; Elumalai Saranya, Elumalai Saranya; Messiah Josephine, Messiah Josephine; Ganesan Sneha, Ganesan Sneha (2023)
A compact planar edge ultra-wideband (UWB) antenna is designed to operate at a frequency range of 3.5 GHz to 10.4 GHz for water quality detection. The design was constructed on an FR4 substrate with an overall dimension of 30 × 35 × 1.6 mm3 . The presented design is used to detect the presence of salt in the water in terms of reflection coefficient (S11). The proposed antenna’s performance was examined by increasing the salinity of the three water samples: distilled water, reverse osmosis (RO), and raw water. The results showed the decrease of the S11 with the increment of salt in the water samples. In addition, the antenna showed good sensitivity as the resonance frequency of the antenna slightly shifted to a lower frequency as the dielectric constant of water increased. Hence, the proposed UWB antenna can be prominently suitable for monitoring water quality and sensors.